2015
DOI: 10.1007/s00253-015-6379-6
|View full text |Cite
|
Sign up to set email alerts
|

Current progress on truffle submerged fermentation: a promising alternative to its fruiting bodies

Abstract: Truffle (Tuber spp.), also known as "underground gold," is popular in various cuisines because of its unique and characteristic aroma. Currently, truffle fruiting bodies are mostly obtained from nature and semi-artificial cultivation. However, the former source is scarce, and the latter is time-consuming, usually taking 4 to 12 years before harvest of the fruiting body. The truffle submerged fermentation process was first developed in Tang's lab as an alternative to its fruiting bodies. To the best of our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Tuber spp., belonging to Ascomycota, are an ectomycorrhizal fungus that lives symbiotically with plants and is characterized by hypogeous fruiting bodies (Mello et al, 2006; Benucci and Bonito, 2016). Their fruiting bodies are also called truffles, and are referred to as “underground gold” because they are rare and are highly valued for their culinary and medicinal traits (Tang et al, 2015). At present, there are at least 180–230 truffle species that have been discovered throughout the world (Kues and Martin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tuber spp., belonging to Ascomycota, are an ectomycorrhizal fungus that lives symbiotically with plants and is characterized by hypogeous fruiting bodies (Mello et al, 2006; Benucci and Bonito, 2016). Their fruiting bodies are also called truffles, and are referred to as “underground gold” because they are rare and are highly valued for their culinary and medicinal traits (Tang et al, 2015). At present, there are at least 180–230 truffle species that have been discovered throughout the world (Kues and Martin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, KMBA is also converted to MTL via demethiolase (also known as C-S lyase), and MTL is spontaneously oxidized to DMS, DMDS and DMTS via the pathway known as the Demethiolation pathway. Our previous work indicated that methionol was the major metabolite produced by the Ehrlich pathway and that DMDS was the major metabolite produced by the Demethiolation pathway 22 36 . (2) The branched chain hydrocarbons of VOCs (i.e., 2-methylbutanal, 3-methylbutanal, 2-methylpropanal and 2-phenylethanol) could be produced from nonsulfur amino acid (i.e., isoleucine, leucine, valine and phenylalanine) through the Ehrlich pathway.…”
Section: Resultsmentioning
confidence: 99%
“…While, both the Ehrlich pathway and Demethiolation pathway operate in truffles are the matter of speculation, and the candidate genes potentially involved have been proposed for T. melanosporum 8 . These would be very useful to construct the metabolite biosynthesis pathway for efficiently aroma-producing during the submerged fermentation of T. melanosporum 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The truffle Tuber spp. establishes ectomycorrhizal (ECM) symbioses with plant roots (e.g., poplar, oak, willow, and shrubs) [ 1–3 ]. The fruit bodies, referred to as truffles, are well-known for their intense aroma, nutritional attributes, and biological activity worldwide [ 4–6 ].…”
Section: Introductionmentioning
confidence: 99%